Albania Social Assistance Policy Note : Key Challenges and Opportunities - Guven, Melis U. (World Bank, Washington, DC, 2013)
Reducing poverty continues to be one of the main priorities of the Government of Albania. Currently, Albania has an ample platform to provide social protection to its citizens through social insurance, social assistance and employment programs. However, these programs are not efficiently linked to each other, which can lead to unclear and occasionally overlapping roles among the programs. Among these social protection programs, Ndihma Ekonomike (NE) is the only poverty-targeted social benefits program available to the Albanian Government, but despite the continued efforts of the Government to improve the program's impact, the poverty impact of NE remains low. Against this backdrop, the objective of this note is to assist the policy makers in Albania with identifying reforms that would improve the overall effectiveness and targeting of NE. Specifically, the note will present key challenges faced by the Government, as well as outline the reforms that would contribute to a more efficient and effective social assistance system in Albania, resulting in a process with improved transparency and accountability. The note is organized as follows: Section 2 presents a brief overview of the social protection system in Albania while at the same time discussing inefficiencies that arise due to lack of linkages between these programs; Section 3 assesses the current effectiveness of NE; and Section 4 concludes with recommendations.